Assessment of Genetic Diversity Among Groundnut (Arachis Hypogaea L.) Genotypes - Namrata; Sharma, Hemlata; Bisen, Prashant; Singh, Bhumica; Jain, Surbhi (International Journal of Bio-resource and Stress Management, 2018)
In present experiment the genetic diversity studied among 30 genotypes of groundnut using D2 statistic during kharif - 2014 in a randomized block design with three replications at the Instructional Farm, College of Technology and Engineering, Maharana Pratap University of Agriculture and Technology, Udaipur for thirteen agro-morphological characters including days to 50% flowering, days to maturity, plant height (cm), number of branches plant-1, number of mature pods per plant, dry pod yield plant-1 (g), kernel yield per plant (g), 100-kernel weight (g), sound mature kernels (%), shelling percentage, biological yield per plant, harvest index (%) and oil content (%). The analysis of variance revealed significant differences among the genotypes for all characters except days to 50% flowering and days to maturity. Based on Ward’s method, 30 genotypes were grouped into two clusters. Cluster I was containing 29 genotypes while cluster II contained only 1 genotype i.e. UG-179. Inter cluster distance between these two clusters was observed 159.68, which proved UG-179 genotype sufficiently different from the rest 29 genotypes. Cluster means revealed that genotypes from these two clusters may be used for future hybrid groundnut breeding programs with special reference to dry pod yield, 100-kernel weight, biological yield, harvest index and oil content. The diversity present among the genotypes helps in producing better high oil groundnut genotypes for the developing countries while low oil genotypes having high confectionary quality also produced as per the demand of groundnut in the developed countries for food purposes.